Drogi, podróżowanie i funkcjonowanie poczty w Rzeczypospolitej Obojga Narodów w XVIII w. z perspektywy przybyszy z Rosji i państw Europy Zachodniej - Ciesielski, Tomasz (In Gremium. Studies in History, Culture and Politics, 2020)
The article presents the technical condition of roads, waterways, bridges, levees and other engineering structures in Poland based on accounts of Russian and other foreign visitors. Land and water means of transport were discussed along with the quality of service offered by Polish and Lithuanian inns valued very poorly by all foreigners. In the 18th century, travelling and communication in the Polish – Lithuanian Commonwealth was a truly fascinating issue. Both Russian and West European visitors saw the country as full of paradoxes, as they encountered many obstacles during their journeys. Dramatically bad condition of roads, terrible inns, poverty of peasants contrasted with ostentatious lavishness of travelling Polish and Lithuanian aristocrats. However, the roads were surprisingly safe and the postal service was extraordinarily efficient and swift even during wartime, going beyond contemporary standards by means of ensuring confidentiality of sent documents. In the 18th century, thanks to the expansion of postal station network, travelling around Poland and Lithuania became not only more comfortable, but also much faster. It was possible to make 60 - 100 km daily, however, transport of goods or marching the army was very troublesome, as then the average pace was approx. 10, max. 15 km daily.